Human Resource Management Strategies for Overcoming Teacher Burnout in Manila - Miguel Paolo C. Evangelista; Maria Clarisse V. Santos (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
This study aims to explore the human resource management (HRM) strategies implemented by educational institutions in Manila to mitigate teacher burnout amidst the pressures of urban environments and digital transformation. This research employed a qualitative approach with an explanatory case study design. Data was gathered through in-depth interviews with HRM managers and teachers at three private secondary schools in Metro Manila, complemented by an analysis of internal policy documents. Data analysis was conducted inductively using data reduction, data display, and conclusion drawing techniques. The research findings revealed three primaries effective HRM strategies: (1) structural support through administrative offloading and hybrid work flexibility, (2) technostress mitigation via digital wellness programs and digital communication ethics, and (3) strengthening organizational culture based on transformational leadership and spiritual values (Animo). These strategies have proven effective in enhancing teacher resilience and reducing emotional exhaustion. Human-centric HRM is the key to sustaining educational quality in urban areas. The implications of this study suggest the need for standardizing educator mental health policies within formal school regulations.